Modified composite nanofiltration membrane as well as preparation method and application thereof

Through the water-phase optimization coupled secondary interface polymerization technology, an active layer with negative charge and rich sulfonate negative ions is formed, which solves the problem that the nanofiltration membrane is difficult to achieve new pollutant retention and mineral ions at the same time, and achieves high-efficiency retention and high-throughput nanofiltration membrane.

CN119701671APending Publication Date: 2025-03-28RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510163310.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing nanofiltration membranes to achieve efficient retention of new pollutants and selective permeability of mineral ions at the same time, and traditional modification methods often lead to a reduction in membrane pore size and a reduction in flux.

Method used

The aqueous phase optimized coupled secondary interfacial polymerization technology is used to form an active layer with negative charge and rich sulfonate negative ions by infiltration and interfacial polymerization on the ultrafiltration base membrane, and the pore size and charge density of the membrane are regulated.

Benefits of technology

The nanofiltration membrane is highly pollutant retention and low mineral salt retention, maintaining good water permeability and high throughput, and is suitable for high-quality drinking water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701671A_ABST
    Figure CN119701671A_ABST
Patent Text Reader

Abstract

The invention provides a modified composite nanofiltration membrane and a preparation method and application thereof.The preparation method comprises the steps that an ultrafiltration base membrane is infiltrated with a water-phase monomer solution, water-phase monomers comprise cyclodextrin compounds and amine compounds, and an infiltrated ultrafiltration base membrane is obtained; contacting the infiltrated ultrafiltration base membrane with a first acyl chloride monomer organic phase, and carrying out a first interfacial polymerization reaction to obtain an original polyamide nanofiltration membrane; and contacting the original polyamide nanofiltration membrane with a second acyl chloride monomer organic phase, and carrying out a second interfacial polymerization reaction to obtain the modified composite nanofiltration membrane. According to the preparation method of the nanofiltration membrane, the operation process is simple, monomers are easy to obtain, the active layer structure of the nanofiltration membrane is optimized through coupling of water phase optimization and a secondary interface polymerization technology, and the obtained nanofiltration membrane is high in water flux, high in new pollutant rejection rate and low in mineral salt permeability and has good application prospects. The method has a good application prospect in high-quality drinking water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and relates to a nanofiltration membrane, in particular to a modified composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] The quality of drinking water not only involves the cleanliness and microbial safety of water, but also includes the removal of harmful substances and the retention of beneficial elements in water. In this context, nanofiltration technology has gradually become an important choice for new water treatment processes due to its high solute selectivity and permeability.

[0003] Nanofiltration membrane technology can usually intercept harmful substances with larger molecular weights, such as organic pollutants, pesticide residues and heavy metals. However, with the continuous emergence of new pollutants, some small molecular organic matter and trace pollutants, with complex structures and small molecular weights, are often difficult to be effectively intercepted by existing nanofiltration membranes, resulting in unsatisfactory removal of new pollutants and becoming a new threat to people's drinking water safety. In addition, current nanofiltration membranes have the phenomenon of "over-retention" of mineral ions in practical applications, especially Ca 2+ Mg 2+ The "ineffective retention" of mineral ions such as ions not only leads to the loss of beneficial mineral ions in the produced water, but also may make the water taste worse, weaken its stability, and even increase the risk of scaling on the concentrated water side, affecting the long-term stable operation of the membrane. In order to avoid this problem, an additional mineralization step is usually required to re-add mineral ions, which increases operating costs and may also have an adverse effect on water quality.

[0004] In order to solve these problems, it is urgent to develop new nanofiltration membrane materials with higher organic matter retention performance and mineral ion permeability. This requires that the nanofiltration membrane can selectively intercept new pollutants while maintaining a low molecular weight cutoff and retain the beneficial mineral ions in the water to the maximum extent. To this end, membrane surface modification technology has become one of the research hotspots in recent years. However, traditional surface modification methods, such as diacyl chloride modification, although they can effectively introduce negative charges, are often accompanied by an increase in the membrane pore size, resulting in a decrease in the separation performance of the membrane.

[0005] In this context, researchers have proposed some new modification methods. CN116272438A discloses a composite nanofiltration membrane and its preparation method and application, which uses sulfonyl chloride to react with the amino or imino groups remaining in the selective separation layer of the nanofiltration membrane prepared by the traditional interfacial polymerization method for amidation reaction (grafting or cross-linking reaction). Sulfonyl chloride reduces the contribution of the amino or imino groups to the positive charge by reacting with the amino or imino groups for amidation reaction, and hydrolyzes to produce sulfonic acid groups that are beneficial to membrane pollution control. Although this method can effectively graft sulfonic acid functional groups to increase the charge density on the membrane surface, it will also lead to excessive reduction of the pore size, which is not conducive to the selective permeation of water and mineral ions.

[0006] CN118477503A discloses a method for preparing a cyclodextrin modified membrane by interfacial polymerization, wherein a cyclodextrin additive is introduced into a piperazine aqueous solution, and the desired nanofiltration membrane is prepared by interfacial polymerization of trimesoyl chloride. Cyclodextrin can affect the interfacial diffusion process of piperazine monomers, and can induce the formation of a thinner and rougher polyamide layer, thereby reducing the total mass transfer resistance and increasing the effective filtration area of ​​the membrane. This method usually leads to a reduction in the retention performance of the nanofiltration membrane, and is not conducive to the selective retention of new pollutants with smaller molecular weights.

[0007] CN108905624A discloses a polyester polyamide amphoteric charge composite nanofiltration membrane and a preparation method thereof, wherein a polysulfone microporous support membrane is treated with macromolecular polyols in sequence, and then trimesoyl chloride and polyethyleneimine are used for two interfacial polymerizations to obtain an amphoteric charge composite nanofiltration membrane. The method forms a negative charge membrane layer by interfacial polymerization of a macromolecular polyol and trimesoyl chloride, and forms a positive charge membrane layer by interfacial polymerization of acyl chloride and polyethyleneimine, thereby making the nanofiltration membrane carry amphoteric charge, improving the filtration performance for inorganic salts, but the pore size of the nanofiltration membrane is relatively large, and although the flux is high, the interception effect of organic pollutants is weakened.

[0008] Therefore, developing a new nanofiltration membrane that can balance the efficient retention of organic matter, especially new pollutants, and the good permeability of mineral ions remains a key problem in current research on drinking water purification technology. Summary of the invention

[0009] The purpose of the present invention is to provide a modified composite nanofiltration membrane and a preparation method and application thereof, optimize the active layer structure of the nanofiltration membrane, and solve the problem that traditional nanofiltration membranes cannot simultaneously achieve efficient retention of new pollutants and selective permeation of mineral ions.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0012] (1) impregnating an ultrafiltration base membrane with an aqueous phase monomer solution, wherein the aqueous phase monomer includes a cyclodextrin compound and an amine compound, to obtain an impregnated ultrafiltration base membrane;

[0013] (2) contacting the wetted ultrafiltration base membrane with a first acyl chloride monomer organic phase to perform a first interfacial polymerization reaction, and washing after the reaction to obtain an original polyamide nanofiltration membrane;

[0014] (3) contacting the original polyamide nanofiltration membrane with a second acyl chloride monomer organic phase to carry out a second interfacial polymerization reaction, and drying after the reaction is completed to obtain the modified composite nanofiltration membrane.

[0015] The preparation method provided by the present invention is based on the water phase optimization coupling secondary interfacial polymerization technology, so as to optimize the structure of the active layer of the nanofiltration membrane. First, cyclodextrin is added to the aqueous phase solution. The cyclodextrin has a special ring structure and is rich in hydroxyl functional groups. It has good compatibility with the polyamide matrix membrane, can significantly improve the hydrophilicity of the nanofiltration membrane, and at the same time, the diffusion of the aqueous phase monomer amine compound can be adjusted to form a hydrophilic active layer. On this basis, a secondary interfacial polymerization reaction is carried out, and the active layer is functionalized with acyl chloride monomers. The cyclodextrin can be arranged in order, and the diffusion of the amine compound in the interfacial polymerization process is regulated to form a more uniform but non-dense nanofiltration membrane. At the same time, due to the regulation of the diffusion of the aqueous phase amine monomer by cyclodextrin, the active layer will have more residual amine groups in the secondary interfacial polymerization reaction to participate in the reaction with the acyl chloride monomer, which is conducive to forming an active layer that is loose in the upper layer and rich in sulfonate anions. At the same time, the abundant hydrophilic cyclodextrin at the bottom of the active layer provides more adsorption sites that are conducive to the interception of new pollutants. Therefore, by coupling the water phase optimization with the secondary interfacial polymerization method, the interception and penetration of the nanofiltration membrane are well balanced.

[0016] Compared with traditional secondary interfacial polymerization, the reaction efficiency is higher, and more charges are accumulated on the membrane surface. Through the coupling of water phase optimization and secondary interfacial polymerization technology, on the one hand, it can avoid the problem of low flux and decreased water permeability after the pore size is reduced by secondary interfacial polymerization of acyl chloride alone. On the other hand, it can solve the problem of reduced membrane retention performance caused by cyclodextrin doping alone. The resulting nanofiltration membrane has good water permeability, improves pollutant retention and facilitates the passage of mineral ions, meeting the nanofiltration membrane treatment needs of high-quality drinking water.

[0017] Preferably, the ultrafiltration base membrane in step (1) comprises a polysulfone ultrafiltration membrane and / or a polyethersulfone ultrafiltration membrane.

[0018] Preferably, the cut-off molecular weight of the ultrafiltration base membrane in step (1) is 30-200 kDa.

[0019] Preferably, the cyclodextrin compound in step (1) includes any one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin, or a combination of at least two of them. Typical but non-limiting combinations include a combination of α-cyclodextrin and β-cyclodextrin, a combination of β-cyclodextrin and γ-cyclodextrin, a combination of α-cyclodextrin and γ-cyclodextrin, or a combination of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0020] Preferably, the amine compound in step (1) comprises piperazine.

[0021] Preferably, in the aqueous monomer solution of step (1), the concentration of the cyclodextrin compound is 1-3wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, in the aqueous monomer solution of step (1), the concentration of the amine compound is 0.2-0.4wt%, for example, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt% or 0.4wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the soaking time in step (1) is 80-100 s, for example, 80 s, 85 s, 90 s, 95 s or 100 s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, in step (2), the first acyl chloride monomer comprises trimesoyl chloride.

[0025] Preferably, in the first acyl chloride monomer organic phase in step (2), the concentration of the first acyl chloride monomer is 0.1-0.3wt%, for example, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt% or 0.3wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the organic solvent of the first acyl chloride monomer organic phase in step (2) comprises any one of n-hexane, cyclohexane or n-heptane, or a combination of at least two of them. Typical but non-limiting combinations include a combination of n-hexane and cyclohexane, a combination of cyclohexane and n-heptane, a combination of n-hexane and n-heptane, or a combination of n-hexane, cyclohexane and n-heptane.

[0027] Preferably, the time of the first interfacial polymerization reaction in step (2) is 20-40 s, for example, 20 s, 25 s, 30 s, 35 s or 40 s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the second acyl chloride monomer in step (3) comprises any one of sulfonyl chloride, oxalyl chloride (OC), malonyl chloride (MC), succinyl chloride (SC), glutaryl chloride (GC) or trimesoyl chloride (TMC), or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sulfonyl chloride and oxalyl chloride, a combination of malonyl chloride and succinyl chloride, a combination of glutaryl chloride and trimesoyl chloride, a combination of sulfonyl chloride, oxalyl chloride and malonyl chloride, or a combination of succinyl chloride, glutaryl chloride and trimesoyl chloride, preferably sulfonyl chloride.

[0029] Preferably, in the second acyl chloride monomer organic phase in step (3), the concentration of the second acyl chloride monomer is 0.5-0.7wt%, for example, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt% or 0.7wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the organic solvent in the second acyl chloride monomer organic phase in step (3) comprises any one of n-hexane, cyclohexane or n-heptane, or a combination of at least two of them. Typical but non-limiting combinations include a combination of n-hexane and cyclohexane, a combination of cyclohexane and n-heptane, a combination of n-hexane and n-heptane, or a combination of n-hexane, cyclohexane and n-heptane.

[0031] Preferably, the time of the second interfacial polymerization reaction in step (3) is 20-40 s, for example, 20 s, 25 s, 30 s, 35 s or 40 s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the drying temperature in step (3) is 20-30°C, for example, 20°C, 22°C, 25°C, 28°C or 30°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] In a second aspect, the present invention provides a modified composite nanofiltration membrane, which is prepared by the preparation method described in the first aspect.

[0034] The modified composite nanofiltration membrane provided by the invention has a negative charge, a charge amount of -30mV to -40mV, an average pore size of 0.25-0.35nm, and a contact angle of 20-30 degrees.

[0035] The charge amount is -30mV to -40mV, for example, it can be -30mV, -32mV, -35mV, -38mV or -40mV, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0036] The average pore size is 0.25-0.35 nm, for example, 0.25 nm, 0.28 nm, 0.30 nm, 0.32 nm or 0.35 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] The contact angle is 20-30°, for example, 20°, 22°, 25°, 28° or 30°, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] In a third aspect, the present invention provides an application of the modified composite nanofiltration membrane described in the first aspect, wherein the modified composite nanofiltration membrane is used for drinking water treatment.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The nanofiltration membrane preparation method provided by the present invention optimizes the active layer structure of the nanofiltration membrane through the coupling of water phase optimization and secondary interfacial polymerization technology. The operation process is simple and the monomers are easy to obtain. The obtained nanofiltration membrane has good water permeability and high water flux, and has high pollutant retention and low mineral salt retention. It has good application prospects for high-quality drinking water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a comparison chart of the nanofiltration performance of the modified composite nanofiltration membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0042] Figure 2 It is a comparison chart of pollutant retention performance of the modified composite nanofiltration membrane prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] In order to clearly illustrate the technical solution of the present invention, in a specific implementation manner, the cut-off molecular equivalent of the polysulfone ultrafiltration base membrane used is 50 kDa.

[0045] Example 1

[0046] This embodiment provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0047] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.3 wt% piperazine and 2 wt% 2-hydroxypropyl β-cyclodextrin for 90 seconds. After the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0048] (2) pouring a 0.2 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane to carry out an interfacial polymerization reaction for 30 s. After the reaction is completed, pouring off the remaining solution on the surface and washing the membrane surface with hexane;

[0049] (3) Immediately pouring a 0.6 wt % sulfonyl chloride n-hexane solution onto the surface of the ultrafiltration membrane to carry out a secondary interfacial polymerization reaction for 30 seconds. After the reaction is completed, pouring off the remaining solution on the surface, and then placing the membrane at room temperature 25° C. to dry for 2 minutes to obtain the modified composite nanofiltration membrane.

[0050] Example 2

[0051] This embodiment provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0052] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.2 wt % piperazine and 1 wt % 2-hydroxypropyl β-cyclodextrin for 100 s. After the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0053] (2) pouring a 0.3 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane to carry out an interfacial polymerization reaction for 20 s. After the reaction is completed, pouring off the remaining solution on the surface and washing the membrane surface with hexane;

[0054] (3) Immediately pouring a 0.5 wt % sulfonyl chloride n-hexane solution onto the surface of the ultrafiltration membrane to carry out a secondary interfacial polymerization reaction for 40 seconds. After the reaction is completed, pouring off the remaining solution on the surface, and then placing the membrane at room temperature 25° C. to dry for 2 minutes to obtain the modified composite nanofiltration membrane.

[0055] Example 3

[0056] This embodiment provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0057] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.4 wt% piperazine and 3 wt% 2-hydroxypropyl β-cyclodextrin for 80 seconds, and after the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0058] (2) pouring a 0.1 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane to carry out an interfacial polymerization reaction for 40 s. After the reaction is completed, pouring off the remaining solution on the surface and washing the membrane surface with hexane;

[0059] (3) Immediately pouring a 0.7 wt % sulfonyl chloride n-hexane solution onto the surface of the ultrafiltration membrane to carry out a secondary interfacial polymerization reaction for 20 seconds. After the reaction is completed, pouring off the remaining solution on the surface, and then placing the membrane at room temperature 25° C. to dry for 2 minutes to obtain the modified composite nanofiltration membrane.

[0060] Example 4

[0061] This embodiment provides a method for preparing a modified composite nanofiltration membrane. Compared with Example 1, the concentration of sulfonyl chloride in step (3) is controlled to be 0.4 wt %, and the rest is the same as Example 1.

[0062] Example 5

[0063] This embodiment provides a method for preparing a modified composite nanofiltration membrane. Compared with Embodiment 1, the concentration of sulfonyl chloride in step (3) is controlled to be 0.8 wt %. The rest is the same as Embodiment 1.

[0064] Example 6

[0065] This embodiment provides a method for preparing a modified composite nanofiltration membrane. Compared with Example 1, the time of the secondary interfacial polymerization reaction in step (3) is controlled to be 1 min, and the rest is the same as Example 1.

[0066] Example 7

[0067] This embodiment provides a method for preparing a modified composite nanofiltration membrane. Compared with Example 1, in the control step (3), the membrane is placed in an oven for drying. The drying conditions are 60° C. for 5 min. The rest are the same as in Example 1.

[0068] Example 8

[0069] This embodiment provides a method for preparing a modified composite nanofiltration membrane. Compared with Example 1, the concentration of 2-hydroxypropyl β-cyclodextrin in step (1) is controlled to be 4 wt %, and the rest is the same as Example 1.

[0070] Comparative Example 1

[0071] This comparative example provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0072] (1) The polysulfone ultrafiltration base membrane was immersed in a 0.3 wt % piperazine aqueous solution for 90 seconds, and then the excess aqueous solution on the surface was removed by a roller until no obvious droplets were present on the surface;

[0073] (2) Pour a 0.2 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane for 30 s. After the reaction, pour off the remaining solution on the surface and place the membrane at room temperature of 25° C. to dry for 2 min to obtain a nanofiltration membrane.

[0074] That is, compared with Example 1, 2-hydroxypropyl β-cyclodextrin is not added in step (1), and the secondary interfacial polymerization in step (3) is not performed. The rest is the same as Example 1.

[0075] Comparative Example 2

[0076] This comparative example provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0077] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.3 wt% piperazine and 2 wt% 2-hydroxypropyl β-cyclodextrin for 90 seconds. After the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0078] (2) Pour a 0.2 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane for 30 s. After the reaction, pour off the remaining solution on the surface and place the membrane at room temperature of 25° C. to dry for 2 min to obtain a nanofiltration membrane.

[0079] That is, compared with Example 1, the secondary interfacial polymerization in step (3) is not performed, and the rest is the same as Example 1.

[0080] Comparative Example 3

[0081] This comparative example provides a method for preparing a modified composite nanofiltration membrane. Compared with Example 1, 2-hydroxypropyl β-cyclodextrin is not added in step (1), and the rest is the same as Example 1.

[0082] Comparative Example 4

[0083] This comparative example provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0084] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.3 wt% piperazine and 1 wt% 2-hydroxypropyl β-cyclodextrin for 90 seconds, and after the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0085] (2) Pour a 0.2 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane for 30 s. After the reaction, pour off the remaining solution on the surface and place the membrane at room temperature of 25° C. to dry for 2 min to obtain a nanofiltration membrane.

[0086] That is, compared with Example 1, the concentration of 2-hydroxypropyl β-cyclodextrin in step (1) is 1 wt %, the secondary interfacial polymerization in step (3) is not performed, and the rest is the same as Example 1.

[0087] Comparative Example 5

[0088] This comparative example provides a method for preparing a modified composite nanofiltration membrane, the preparation method comprising the following steps:

[0089] (1) The polysulfone ultrafiltration base membrane was immersed in an aqueous solution of 0.3 wt % piperazine and 4 wt % 2-hydroxypropyl β-cyclodextrin for 90 s. After the immersion, the excess aqueous solution on the surface was removed with a roller until no obvious droplets were present on the surface of the base membrane;

[0090] (2) Pour a 0.2 wt % hexane solution of trimesoyl chloride onto the surface of the soaked ultrafiltration membrane for 30 s. After the reaction, pour off the remaining solution on the surface and place the membrane at room temperature of 25° C. to dry for 2 min to obtain a nanofiltration membrane.

[0091] That is, compared with Example 1, the concentration of 2-hydroxypropyl β-cyclodextrin in step (1) is 4 wt %, the secondary interfacial polymerization in step (3) is not performed, and the rest is the same as Example 1.

[0092] Performance Testing

[0093] The modified composite nanofiltration membranes prepared in the examples and comparative examples were subjected to nanofiltration performance tests, and the flux and retention rate of the nanofiltration membranes were calculated.

[0094] The nanofiltration performance test was carried out by a pressure-driven cross-flow nanofilter. The test temperature and pressure were 25°C and 0.6MPa, respectively. The concentration of sodium sulfate solution was 1000ppm, the concentration of calcium chloride was 1000ppm, and the concentration of magnesium chloride was 1000ppm.

[0095] The calculation formula of flux (J) is as follows:

[0096]

[0097] Where, J is the membrane flux (LMH), S is the effective test area of ​​the membrane (m 2 ), t is the operation time (s), and V is the volume of liquid that passes through during the time t (L).

[0098] The retention rate (R) is calculated as follows:

[0099]

[0100] Among them, C0 and C p are the solute concentrations of the feed solution and the permeate, respectively, and the solute concentrations are measured by a conductivity meter.

[0101] Figure 1 It is a comparison chart of the membrane flux and the retention rate of mineral salts of the modified composite nanofiltration membranes prepared in Example 1, Comparative Example 1 and Comparative Example 2. Among them, PIP-TMC represents Comparative Example 1, PIP+2CD represents Comparative Example 2, and PIP+2CD+TMC-SC represents Example 1.

[0102] The test results are listed in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] The nanofiltration performance of the pollutants prepared in the examples and comparative examples was tested, and the retention rate was calculated. The test conditions were: the test was carried out by a pressure-driven cross-flow nanofiltration instrument, the test temperature and pressure were 25°C and 0.6MPa, respectively, the influent concentration of different pollutants was 10ppb, and the retention rate was calculated in the same way as above.

[0107] Figure 2 It is a comparison chart of pollutant retention rates of Example 1, Comparative Example 1 and commercially available membrane NF270.

[0108] Wherein, PIP-TMC represents Comparative Example 1, PIP+CD+TMC-SC represents Example 1, ATLJ represents atrazine, SMZ represents sulfamethoxazole, CMZ represents carbamazepine, EM represents erythromycin, and TMP represents trimethoprim.

[0109] The results are listed in Table 2.

[0110] Table 2

[0111]

[0112] It can be seen from Tables 1 and 2 that the composite nanofiltration membrane prepared by the present invention has a high flux, and the optimal flux can reach 29.3LMH / bar. At the same time, it maintains a high sodium sulfate retention rate, an organic pollutant retention rate, and a relatively low calcium and magnesium ion retention, which is conducive to the passage of mineral ions. Under the optimal conditions, the sodium sulfate retention rate can reach 99.2%, the organic pollutant retention rate can reach more than 80%, and the calcium and magnesium ion retention rate is controlled below 40%. It has good high pollutant retention and low mineral retention, and has good drinking water treatment performance.

[0113] Compared with Example 1, in Examples 4 and 5, changing the concentration of sulfonyl chloride will increase the surface charge of the membrane, which is conducive to the passage of mineral ions, but too high a concentration of sulfonyl chloride may reduce the membrane pore size, which is not conducive to water penetration; in Example 6, the longer the reaction time of sulfonyl chloride, the more complete the reaction will be, the more negatively charged the membrane will be, and the lower the mineral ion retention will be, but it will also lead to too small a pore size and reduce water flux; in Example 7, drying at a higher temperature may further produce thermal cross-linking in the membrane, resulting in a reduced pore size, reduced flux, and reduced sodium sulfate retention; in Example 8, too high a cyclodextrin concentration will reduce the membrane retention rate. In some of the above examples, although low calcium and magnesium retention is shown, its sodium sulfate retention is low, indicating that its retention molecular weight is small, the retention rate for pollutants is also low, and the performance of pollutant retention is low.

[0114] In Comparative Example 1, without adding cyclodextrin and without performing secondary interfacial polymerization, the membrane flux and pollutant retention performance are significantly low, and the calcium and magnesium retention is relatively high; in Comparative Example 2, without performing secondary interfacial polymerization, although a relatively low calcium and magnesium retention is maintained, the retention rates of sodium sulfate and pollutants are generally too low, indicating that the molecular weight retention is small; in Comparative Example 3, secondary interfacial polymerization is performed without adding cyclodextrin, and its various performances are still unqualified. In Comparative Examples 4-5, without performing secondary interfacial polymerization, even if the concentration of cyclodextrin is adjusted, the performance of the membrane cannot be improved. This shows that the addition of cyclodextrin has an important regulatory and promoting effect on secondary interfacial polymerization. Only under the synergistic effect of cyclodextrin and secondary interfacial polymerization can excellent retention performance be achieved, so that the nanofiltration membrane can simultaneously achieve the excellent performance of high pollutant retention and low mineral retention.

[0115] In summary, the nanofiltration membrane preparation method provided by the present invention optimizes the active layer structure of the nanofiltration membrane through the coupling of water phase optimization and secondary interfacial polymerization technology. The operation process is simple and the monomers are easy to obtain. The obtained nanofiltration membrane has good water permeability and high water flux, as well as high pollutant retention and low mineral salt retention, and has good application prospects for high-quality drinking water treatment.

[0116] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a modified composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: (1) impregnating an ultrafiltration base membrane with an aqueous phase monomer solution, wherein the aqueous phase monomer includes a cyclodextrin compound and an amine compound, to obtain an impregnated ultrafiltration base membrane; (2) contacting the wetted ultrafiltration base membrane with a first acyl chloride monomer organic phase to perform a first interfacial polymerization reaction, and washing after the reaction to obtain an original polyamide nanofiltration membrane; (3) contacting the original polyamide nanofiltration membrane with a second acyl chloride monomer organic phase to carry out a second interfacial polymerization reaction, and drying after the reaction is completed to obtain the modified composite nanofiltration membrane.

2. The preparation method according to claim 1, characterized in that: The ultrafiltration base membrane in step (1) comprises a polysulfone ultrafiltration membrane and / or a polyethersulfone ultrafiltration membrane; Preferably, the cut-off molecular weight of the ultrafiltration base membrane in step (1) is 30-200 kDa.

3. The preparation method according to claim 1 or 2, characterized in that: The cyclodextrin compound in step (1) includes any one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin, or a combination of at least two thereof; Preferably, in the aqueous monomer solution of step (1), the concentration of the cyclodextrin compound is 1-3 wt %.

4. The preparation method according to any one of claims 1 to 3, characterized in that The amine compound in step (1) comprises piperazine; Preferably, in the aqueous monomer solution of step (1), the concentration of the amine compound is 0.2-0.4 wt %; Preferably, the infiltration time in step (1) is 80-100 s.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (2) the first acyl chloride monomer comprises trimesoyl chloride; Preferably, in the first acyl chloride monomer organic phase in step (2), the concentration of the first acyl chloride monomer is 0.1-0.3 wt %.

6. The preparation method according to any one of claims 1 to 5, characterized in that: Step (2) the organic solvent of the first acyl chloride monomer organic phase comprises any one of n-hexane, cyclohexane or n-heptane, or a combination of at least two thereof; Preferably, the time of the first interfacial polymerization reaction in step (2) is 20-40 seconds.

7. The preparation method according to any one of claims 1 to 6, characterized in that: Step (3) the second acyl chloride monomer comprises any one of sulfonyl chloride, oxalyl chloride, malonyl chloride, succinyl chloride, glutaryl chloride or trimesoyl chloride, or a combination of at least two thereof; Preferably, in the second acyl chloride monomer organic phase in step (3), the concentration of the second acyl chloride monomer is 0.5-0.7 wt %; Preferably, the organic solvent in the second acyl chloride monomer organic phase in step (3) comprises any one of n-hexane, cyclohexane or n-heptane, or a combination of at least two of them.

8. The preparation method according to any one of claims 1 to 7, characterized in that: Step (3) The time of the second interfacial polymerization reaction is 20-40s; Preferably, the drying temperature in step (3) is 20-30°C.

9. A modified composite nanofiltration membrane, characterized in that: The modified composite nanofiltration membrane is prepared by the preparation method described in any one of claims 1-8.

10. An application of the modified composite nanofiltration membrane according to claim 9, characterized in that: The modified composite nanofiltration membrane is used for drinking water treatment.

Citation Information

Patent Citations

  • Polyester polyamide amphoteric charge composite nanofiltration membrane and preparation method thereof

    CN108905624A

  • Composite nanofiltration membrane as well as preparation method and application thereof

    CN116272438A

  • Method for optimizing property of polyamide composite membrane

    CN102188915A

  • Cyclodextrin modified polyamide film composite film, and preparation method and application thereof

    CN111359455A

  • Interfacial polymerization preparation method of cyclodextrin modified membrane

    CN118477503A